Emerging global partnership: Brazil and China - Haibin,Niu (2010)
The Lula era has witnessed a changing bilateral strategic partnership between China and Brazil, having the interlocutions between both countries became more substantial, comprehensive and influential. To enlarge the global impacts of the partnership, both countries should inject more regional and global components into their bilateral agenda. In doing so, both sides need to enhance the ties not only in terms of economic cooperation but also of social interaction